Translating knowledge to attitude: a survey on the perception of bystander cardiopulmonary resuscitation among dental students in Universiti Sains Malaysia and school teachers in Kota Bharu, Kelantan. - Chew, K S; Yazid, Mohd Noh Abu; Kamarul, B.A.; Rashidi, A. (Malaysian Medical Association (MMA), 2009)
This voluntary, anonymous questionnaire survey was performed to assess the willingness of Basic Life Support (BLS) participants to perform bystander cardiopulmonary resuscitation (CPR). A total of 55 dental students and 73 school teachers were assessed on their willingness to perform bystander CPR after completion of their BLS training. In general, only 29.0% of the total 128 participants said that they would offer to perform CPR under any cardiac arrest condition and 69.0% said that they would just offer to call the ambulance but they would not offer to perform CPR. When analyzed separately, only 16.4% of school teachers said that they would perform CPR as compared to 45.5% of dental students (p < 0.001). Knowing how to perform CPR does not necessarily translate into willingness to perform CPR.